Nanocomposite chitosan hydrogels based on PLGA nanoparticles as potential biomedical materials. (February 2018) - Santos, Talitha Caldas dos; Hernández, Rebeca; Rescignano, Nicoletta; Boff, Laurita; Reginatto, Flávio Henrique; Simões, Cláudia Maria Oliveira; de Campos, Angela Machado; Mijangos, Carmen
Graphical abstract: Highlights: Transparent chitosan/PLGA nanoparticles composites hydrogels were synthesized. Morphology, mechanical properties and cytotoxicity were investigated. Nanocomposites hydrogels were able to form a homogeneous matrix. FTIR spectra confirmed the nanoparticles presence in the chitosan matrix. It suggests that these hydrogels may be used as dosage forms for buccal delivery. Abstract: We report on the preparation and characterization of nanocomposite chitosan hydrogels with embedded poly (lactic-co-glycolic acid) (PLGA) nanoparticles employed for encapsulation of an enriched flavonoid fraction of Cecropia glaziovii Snethl. As a first step, the experimental conditions to obtain homogeneous chitosan hydrogels at 37 °C through gelation with NaHCO3 were optimized. Then, nanocomposite chitosan hydrogels were prepared through direct incorporation of nanoparticlesat different concentrations ranging from 1 to 10% w/w to gelling aqueous chitosan solutions. The resulting hydrogels were characterized through Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), oscillatory rheological experiments and cytotoxicity tests. FT-IR spectra confirmed the PLGA nanoparticles presence within the chitosan matrix through the absorption peak located at 1750 cm −1 . The presence of the PLGA nanoparticles decreased the thermal stability of the nanocomposite chitosan hydrogels compared to the pure chitosan hydrogel. SEM images allowed observing porous matrixes where nanoparticles appeared to be homogeneously dispersed. The elastic moduli found for nanocomposite chitosan hydrogels varied with the PLGA nanoparticles concentration with a maximum at 3% nanoparticles concentration. Cytotoxicity tests revealed that after 48 h, neither thepure hydrogel nor the nanocomposite chitosan hydrogels with 10% nanoparticles concentration showed toxicity on VERO cells.